In Vitro Release Study on Capsules and Tablets Containing Enteric - Coated Granules Prepared by Wet Granulation - B. H. Al-Khedairy, Eman (Iraqi Journal of Pharmaceutical Sciences, 2017)
Wet granulation method was used instead of conventional pan coating or fluidized –bed coating technique to prepare enteric-coated diclofenac sodium granules, using ethanolic solution of EudragitTM L100 as coating, binding and granulating agent .Addition of PEG400 or di-n-butyl phthalate as a plasticizer was found to improve the enteric property of the coat.Part of the resulted granules was filled in hard gelatin capsules (size 0), while the other part was compressed into tablets with and without disintegrant.The release profile of these two dosage forms in 0.1N HCl (pH 1.2)for 2 hours, and in phosphate buffer (pH 6.8) for 45 minutes as well as the release kinetic were compared with that of the enteric film coated Voltadin (R) SDI tablets.The results of this study show that, the prepared dosage forms have a good enteric property, with faster release of drug from encapsulated enteric-coated granules in comparison with compressed tablets.